Mesoclemmys vanderhaegei (Bour 1973) Vanderhaege´s Toad-headed Turtle, Karumbé-hy. - Marques, Thiago S. (2014)
Vanderhaege’s Toad-headed Turtle, Mesoclemmys vanderhaegei (Family Chelidae), is a poorly known freshwater turtle that is widely distributed in central South America. It occurs in the Amazonas, Tocantins, Paraguay, Parana, and Uruguay River basins, where it inhabits shallow streams, ponds, and marshes. Its taxonomic status has long been uncertain and confusion with similar looking species of toad-headed turtles still occurs frequently, leading to erroneous distribution records. Adults can reach up to 285 mm straight carapace length. No subspecies are currently recognized, although there are obvious differences in shell, iris coloration, and body size among populations. The species seems to rely mainly on a carnivorous or opportunistic omnivorous diet. Females are capable of depositing more than one clutch per year with a mean clutch size of 6.4 ± 3.9 eggs. Due to its great ecological adaptability, the species occurs in pristine habitats as well as agricultural and urban areas, but with a cryptic lifestyle. There is little known about its basic ecology except for local studies in Brazil, but detailed ecological surveys in Paraguay and Argentina are lacking. The current population status cannot be fully determined.